Adolescência, escola e pandemia: contribuição da psicanálise à educação - Marcos Venancio Mendes (2021)
This psychoanalytic research addresses the effects of social distancing resulting from the Covid-19 pandemic, in the crossing and constitution subjective perception of public school students. The work aimed to general verify how these subjects dealt with the implications arising of this time of uncertainty and anguish reverberated by the pandemic, leaving, for this, from their own speeches. It also sought to identify the emergence of segregation movements that could ensure to relate this phenomenon to the adolescent subject experience in the school context. As methodological design, five virtual conversation meetings were held with four teenagers, two female and two male. The conversations were carried out through a video calls application. As a result, the study demonstrated the ambivalent character of segregation, now appearing as a structuring dimension of relations human beings, sometimes as a speech effect. In addition, the survey indicated how much the lack of physical space from the school is felt by these adolescents, as a place permeated with possibilities to (re) invent themselves in the face of the turbulent adolescence time; signaled by the non-adaptability of these young people to Emergency Remote Teaching. The importance of school in the adolescent crossing as a place that spontaneously influences the psychic constitution of these individuals. And, finally, it pointed out the need for circulation of the word and listening to the individuals inserted in this context, as movements that the school should appropriate and before which psychoanalysis can contribute, in view of its theoretical-methodological path.